Runx1 Deficiency Protects Against Adverse Cardiac Remodeling After Myocardial Infarction. Issue 1 (2nd January 2018) - McCarroll, Charlotte S.; He, Weihong; Foote, Kirsty; Bradley, Ashley; Mcglynn, Karen; Vidler, Francesca; Nixon, Colin; Nather, Katrin; Fattah, Caroline; Riddell, Alexandra; Bowman, Peter; Elliott, Elspeth B.; et al.
Abstract : Background: Myocardial infarction (MI) is a leading cause of heart failure and death worldwide. Preservation of contractile function and protection against adverse changes in ventricular architecture (cardiac remodeling) are key factors to limiting progression of this condition to heart failure. Consequently, new therapeutic targets are urgently required to achieve this aim. Expression of the Runx1 transcription factor is increased in adult cardiomyocytes after MI; however, the functional role of Runx1 in the heart is unknown. Methods: To address this question, we have generated a novel tamoxifen-inducible cardiomyocyte-specific Runx1 -deficient mouse. Mice were subjected to MI by means of coronary artery ligation. Cardiac remodeling and contractile function were assessed extensively at the whole-heart, cardiomyocyte, and molecular levels. Results: Runx1 -deficient mice were protected against adverse cardiac remodeling after MI, maintaining ventricular wall thickness and contractile function. Furthermore, these mice lacked eccentric hypertrophy, and their cardiomyocytes exhibited markedly improved calcium handling. At the mechanistic level, these effects were achieved through increased phosphorylation of phospholamban by protein kinase A and relief of sarco/endoplasmic reticulum Ca 2+ -ATPase inhibition. Enhanced sarco/endoplasmic reticulum Ca 2+ -ATPase activity in Runx1-deficient mice increased sarcoplasmic reticulum calcium content and sarcoplasmic reticulum–mediated calcium release, preserving cardiomyocyte contraction after MI. Conclusions: Our data identified Runx1 as a novel therapeutic target with translational potential to counteract the effects of adverse cardiac remodeling, thereby improving survival and quality of life among patients with MI. Abstract : Supplemental Digital Content is available in the text.